A Study of the Needs Conditions for Development of a Combined Model of Active Proactive Learning with KWDL Techniques to Enhance Mathematical Problem Solving Skills for Junior High School Students - Mansup, Maitri; Meesup, Phutcharawalai; Rimcholakarn, Yuporn (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
The purpose of this research was to study the needs development of a combined model of active proactive learning with KWDL techniques to enhance mathematical problem solving skills. The samples were 180 mathematics teachers teaching Junior High School students in Secondary Educational Service Area Office 41. They were selected by using Taro Yamane formula with 95% confidence level with Multi - state Random Sampling by the sizes of schools: large, medium or small. The instruments used were questionnaires about the needs development of a combined model of active proactive learning with KWDL techniques to enhance mathematical problem solving skills and analyzed using frequency, percentage, mean ( ), standard deviation (S.D.) and Modified Priority Needs Index by using Modified Priority Need Inbox Technique. The results of this research were as follows: real conditions of a combined model of active proactive learning with KWDL techniques to enhance overall mathematical problem solving skills were in a high level and practice conditions of the teachers had the highest level of active proactive learning with KWDL techniques to enhance overall mathematical problem solving skills.